MENINGKATKAN KETERAMPILAN SERVIS BAWAH PERMAINAN BOLA VOLI MELALUI STRATEGI PEMBELAJARAN BERDIFERENSIASI PESERTA DIDIK KELAS X SMK N 7 SEMARANG - Faturohman, Ahmad; Hadi, Husnul (YLPK Mahardhika, 2024)
The purpose of this study is to improve student learning outcomes, especially the psychomotor aspect, namely lower service skills in volleyball games in class X of SMK Negeri 7 Semarang. Differentiated learning methods are used in this study. This class action research involved 36 students in class X of SMK Negeri 7 Semarang. The source of data for learning outcomes is an evaluation carried out at the end of each learning cycle and findings from teachers who teach physical education subjects in class X. Instrument to collect data through observation. documentation and tools for assessing under-service skills. Qualitative descriptive forms are used to analyze research data. documentation and tools for assessing under-service skills. Qualitative descriptive forms are used to analyze research data. The stages of data presentation include data reduction, data appearance, and conclusion drawn. The data triangulation method is used to test the validity of the data. The results of the study showed that class X students who used differentiated learning had better volleyball serving skills. In the pre-cycle, the completeness of the students' scores was 41.67%, increased to 69,44% in the first cycle, and increased again to 80,56% in the second cycle. The average score before the action was 67, but it increased to 84 in cycle II. Therefore, the research has been successful. Class X students of SMK Negeri 7 Semarang have improved their bottom service skills in volleyball games by using differentiated learning strategies.